2017
DOI: 10.1371/journal.pone.0189842
|View full text |Cite
|
Sign up to set email alerts
|

Fetal head size and effect of manual perineal protection

Abstract: ObjectiveThe aim of this study was to evaluate whether a previously identified modification of Viennese method of perineal protection remains most effective for reduction of perineal tension in cases with substantially smaller or larger fetal heads.MethodsA previously designed finite element model was used to compare perineal tension of different modifications of the Viennese method of perineal protection to "hands-off" technique for three different sizes of the fetal head. Quantity and extent of tension throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
(64 reference statements)
0
25
1
Order By: Relevance
“…Indeed, computational analysis revealed that the degree of reduction in perineal strain at the fourchette is a determinant of where the thumb and index finger are placed on the perineum as well as the distance and direction of their medial movements. Based on measures of maximum perineal strain, minor alterations in these parameters were associated with a gradual reduction in the maneuver’s efficacy . Interestingly, all the respondents who provided correct and complete information about the MPP technique had <5 years’ work experience in maternity care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, computational analysis revealed that the degree of reduction in perineal strain at the fourchette is a determinant of where the thumb and index finger are placed on the perineum as well as the distance and direction of their medial movements. Based on measures of maximum perineal strain, minor alterations in these parameters were associated with a gradual reduction in the maneuver’s efficacy . Interestingly, all the respondents who provided correct and complete information about the MPP technique had <5 years’ work experience in maternity care.…”
Section: Discussionmentioning
confidence: 99%
“…Based on measures of maximum perineal strain, minor alterations in these parameters were associated with a gradual reduction in the maneuver's efficacy. 20,21 Interestingly, all the respondents who provided correct and complete information about the MPP technique had <5 years' work experience in maternity care. This information is particularly important for maternity units planning to adopt MPP because it highlights the importance of targeting all staff levels, irrespective of years of experience, when devising effective interventions for the implementation of MPP policy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has previously demonstrated that, during FMPP, the optimal placement of the thumb and index finger is two cm anterior of the fourchette and 12 cm apart. While the most effective distance and direction of movement is to approximate these digits by a distance of one cm on either side without changing their antero-posterior orientation to the fourchette [17,20,21,23]. Additionally, it has been also shown, that an imprecision of just one cm might increase the maximum strain at the perineum by up to 30% [20].…”
Section: Comparison To Other Studiesmentioning
confidence: 99%